Primary Care Provider Continuity Is Associated With Improved Preventive Service Ordering During Brief Visits for Acute Symptoms - John C. Matulis; Jason J. Schilling; Frederick North (SAGE Publishing, 2019)
Background: If a patient presents for an acute care visit and sees their assigned primary care provider (PCP), they may be more likely to receive preventive and other services than a patient not seeing their assigned PCP. Methods: After exclusion of 2 visits with insufficient information, we reviewed 98 consecutive, outpatient internal medicine 15-minute acute care visits comparing patients seeing their assigned PCP with those seeing a non-PCP provider. The primary outcome, preventive service ordering, was measured in 2 ways: percentage of patient visits with any preventive service ordered and the total number of preventive services ordered as a proportion of all preventive service items due for each entire cohort. The secondary outcome of other work completed was assessed by comparing tests and consults ordered, and by counting the number of physical examination elements and discrete medical diagnoses documented. Results: The PCPs were significantly more likely than non-PCPs to order any preventive service 45% versus 17% ( P = .005; odds ratio [OR]: 4.16, 95% confidence interval [CI]: 1.45-12.0). The PCP cohort ordered a higher proportion of the total number of preventive services due compared with the non-PCP cohort (30% vs 11%; P = .002; OR: 3.4, CI: 1.5-7.7). The PCPs also addressed more medical diagnoses (2.3 vs 1.4; P = .008) and more frequently ordered tests outside the reason for that visit (40% vs 13%; P = .003; OR: 4.27, CI: 1.5-11.8). Conclusion: Patients seeing their assigned PCP in brief, acute visits have higher rates of preventive and other service ordering compared to those not seeing their assigned PCP.